The COVID-19 pandemic response and its impact on post-corona health emergency and disaster risk management in Italy - Lamberti-Castronuovo, Alessandro; Parotto, Emanuela; Della Corte, Francesco; Hubloue, Ives; Ragazzoni, Luca; Valente, Martina (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic has profoundly impacted societies, influencing countries' Health Emergency and Disaster Risk Management (H-EDRM) systems. By taking Italy as a case study, this research aimed to investigate the response to the COVID-19 pandemic, focusing on the changes made to the existing H-EDRM system, with an emphasis on human resources, health service delivery, and logistics and the forward-looking strategies for the next health emergencies and disasters. Methods We performed a retrospective observational case study using qualitative methodology. Data was collected via semi-structured interviews and analyzed considering the World Health Organization (WHO) H-EDRM framework. Multiple interviewees were selected to obtain a holistic perspective on the Italian response to COVID-19. Stakeholders from five different sectors (policy-making, hospital, primary care, third sector, lay community) from three of the most impacted Italian regions (Piemonte, Lombardia, and Veneto) were interviewed, for a total of 15 respondents. Results Results on human resources revolved around the following main themes: personnel, training, occupational health, and multidisciplinary work; results on health service delivery encompassed the following main themes: public health, hospital, and primary care systems; results on logistics dealt with the following themes: infrastructures, supplies, transports, and communication channels. Lessons learned stressed on the importance of considering pragmatic disaster preparedness strategies and the need for cultural and structural reforms. Stakeholders mentioned several implications for the post-pandemic H-EDRM system in Italy. Conclusions Findings highlight that the interconnection of sectors is key in overcoming pandemic-related challenges and for future disaster preparedness. The implications for the Italian H-EDRM system can inform advancements in disaster management in Italy and beyond.